2014
DOI: 10.1007/s10608-014-9650-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Suicide Among Treatment Seeking Adolescents: The Role of Positive and Negative Affect Intensity

Abstract: Risk for suicide among adolescents remains a serious public health concern. Despite the relevance of individual differences in affective experience to clinically relevant problems generally, and risk for suicide more specifically, relatively little work has evaluated affect intensity in relation to adolescent risk for suicide. To address this notable gap in the literature, the current study evaluated the unique associations between dimensions of affect intensity and risk for suicide in a sample of 165 treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…High frequency and intensity of positive emotions, low frequency and intensity of negative emotions, instability of positive and negative emotions, and low emotional clarity have been associated with poor psychological outcomes in adolescents, including depression, anxiety, and suicidality (e.g., Rojas, Leen-Feldner, Blumenthal, Lewis, & Feldner, 2015;Salguero, Palomera, & Fernández-Berrocal, 2012;Silk, Steinberg, & Morris, 2003;van Roekel et al, 2016). The exploration of normative patterns of adolescent emotional development in the present review will hopefully pave the way to a better understanding of abnormal emotional experience, thus informing treatment research and clinical work.…”
mentioning
confidence: 85%
“…High frequency and intensity of positive emotions, low frequency and intensity of negative emotions, instability of positive and negative emotions, and low emotional clarity have been associated with poor psychological outcomes in adolescents, including depression, anxiety, and suicidality (e.g., Rojas, Leen-Feldner, Blumenthal, Lewis, & Feldner, 2015;Salguero, Palomera, & Fernández-Berrocal, 2012;Silk, Steinberg, & Morris, 2003;van Roekel et al, 2016). The exploration of normative patterns of adolescent emotional development in the present review will hopefully pave the way to a better understanding of abnormal emotional experience, thus informing treatment research and clinical work.…”
mentioning
confidence: 85%
“…For instance, a number of authors have suggested that negative affectivity (i.e., the tendency to experience a wide range of negative emotions) is strongly linked to narcissism, since the instability of the perception of one's value is fluctuating and strongly dependent on feedbacks from the outside world (Rhodenwalt, Madrian & Cheeney, 1998). Furthermore, considering that depressive symptoms and negative affectivity are considered considerable risk factors for suicide ideation and behaviors (Mackenzie et al, 2011;Rojas et al, 2015), along with the fact that depression is the most common diagnosis among young adult suicidal people (Brent et al, 2002), we hypothesize that negative affectivity may act as a confounding variable in the relationship between narcissism and suicide ideation.…”
Section: Suicide In Narcissistic Personalitiesmentioning
confidence: 99%
“…That is, people can take control of their mood states, regulate how much and how long particular mood states will persist, and regulate the expression of particular moods”. Among treatment seeking adolescents it was found that difficulties in experiencing positive affect and a high intensity of negative affect was correlated with increased suicidality [ 20 ]. Dysfunctional processing of autobiographical memories such as bias for negative emotional memories and difficulties in retrieving positive memories is also found in depressed adults [ 21 ].…”
Section: Introductionmentioning
confidence: 99%